Cognitive, Motor, and Language Development of Preschool Children With Craniofacial Microsomia. (September 2021) - Collett, Brent R.; Wallace, Erin R.; Kapp-Simon, Kathleen A.; Johns, Alexis L.; Drake, Amelia F.; Heike, Carrie L.; Kinter, Sara; Luquetti, Daniela V.; Magee, Leanne; Norton, Susan; Sie, Kathleen; Speltz, Matthew L.
Objective: To examine neurodevelopment in preschool-aged children with craniofacial microsomia (CFM) relative to unaffected peers. Design: Multisite, longitudinal cohort study. Setting: Tertiary care centers in the United States. Participants: We included 92 children with CFM ("cases") through craniofacial centers and clinics. Seventy-six children without CFM (controls) were included from pediatric practices and community advertisements. This study reports on outcomes assessed when participants were an average age of 38.4 months (SD = 1.9). Main outcome measures: We assessed cognitive and motor skills using the Bayley Scales of Infant and Toddler Development, third edition (Bayley-III), and language function using subtests from the Clinical Evaluation of Language Fundamentals—Preschool, second edition (CELF-P2). Results: Case–control differences were negligible for Bayley-III cognitive (effect sizes [ES] = −0.06, P = .72) and motor outcomes (ES = −0.19, P = .25). Cases scored lower than controls on most scales of the CELF-P2 (ES = −0.58 to −0.20, P = .01 to .26). Frequency counts for "developmental delay" (ie, one or more scores > 1 SD below the normative mean) were higher for cases (39%) than controls (15%); however, the adjusted odds ratio = 1.73 ( P = 0.21) was not significant. Case–control differences were most evident in children with microtia or other combinations of CFM-related facial features. Conclusions: Cognitive and motor scores were similar for preschool-aged children with and without CFM. However, children with CFM scored lower than controls on language measures. We recommend early monitoring of language to identify preschoolers with CFM who could benefit from intervention.